Low noise design and acoustic testing of the airbus helicopter H160-B - Guntzer, F.; Gareton, V.; Pinacho, J.P.; Caillet, J. (My University, 2019)
The noise certification and low noise levels of the newly developed Airbus Helicopters model, the H160-B, are presented in this paper. In the first part, the helicopter low-noise characteristics, as well as the certification methodology are described. In the second part, the noise certification results of the helicopter are presented and compared to available world fleet data, underlining the low noise levels of the H160-B helicopter. A detailed analysis, focusing on the approach condition, is then presented in a third part, relying on one hand on measurement data treated with a time-based source separation software (ROSI) and on the second hand on comprehensive code (ONERA HMMAP) numerical results. This analysis allows again validating of the effectiveness of the Blue Edge™ main rotor blade design in terms of noise